Pharmaceutical assistance programs to support smoking cessation medication access - León Salas, Angie Rebeca (2017)
OBJECTIVES: Rural smokers are more likely to be uninsured and live in poverty, which may pose significant cost barriers to accessing smoking cessation medications. As part of a randomized clinical trial, we provided support to connect low-income smokers with the use of pharmaceutical assistance programs (PAPs) to improve medication access. METHODS: Study participants were rural smokers enrolled in a randomized clinical trial testing in-office telemedicine versus telephone-based approaches to deliver counseling sessions. For potentially qualified participants, we developed a system to connect them with PAPs that provided smoking cessation medications at low or no cost. Participants reported medication utilization 3 and 6 months after randomization. RESULTS: Of the 560 study participants, 312 (55.7%) met initial screening criteria for PAP eligibility. Of those eligible, 104 (33.3%) initiated a PAP application, with 49 (15.7%) completing the application and ultimately receiving medications through the programs. Despite the availability of assistance with the PAP application process, overall medication use among those that were eligible for PAP was significantly lower than among participants with higher incomes or access to prescription insurance (60.4% vs. 51.3%; P = 0.04). Abstinence among PAP-eligible smokers was also lower at the 3-month follow-up (P = 0.01), but this difference was not present at the 6- and 12-month follow-up surveys. CONCLUSION: With substantial assistance, some low-income smokers without prescription insurance can get effective smoking cessation medications through PAPs, but overall access remains worse than among those with higher incomes or prescription insurance.